PENGARUH KEAKTIFAN BERORGANISASI DAN KEMAMPUAN KOMUNIKASI INTERPERSONAL TERHADAP PRESTASI AKADEMIK MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN STAMBUK 2021 - Lidya Theresia Benedigta Silitonga; Tauada Silalahi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study is the existence of negative perceptions among some students regarding participation in student organizations, which is considered to interfere with study focus, as well as variations in interpersonal communication skills that affect students’ academic achievement. Therefore, this study aims to examine the effect of Organizational Activeness and Interpersonal Communication Ability on the academic achievement of 2021 Stambuk Office Administration Education students. This research was conducted at the State University of Medan. This type of research is ex post facto, with the sampling technique using total sampling or the entire population of 88 students. The data collection instruments were observation, documentation, and a questionnaire. Instrument testing used validity and reliability tests conducted with SPSS software version 31. The data analysis techniques included normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination, and hypothesis testing using t-test and F-test with SPSS version 31. The result of multiple linear regression calculations shows that partially, organizational activeness (X₁) has a positive and significant effect on academic achievement, with tcount= 5.981 > ttable = 1.676 and α = 0.000 < 0.05. Interpersonal communication ability (X₂) also has a positive and significant effect on academic achievement, with tcount = 14.613 > ttable = 1.676 and α = 0.000 < 0.05. Simultaneously, both variables have a positive and significant effect on academic achievement, with Fcount = 2910.699 > F_table = 3.18 and α = 0.000 < 0.05, and the contribution of the independent variables to students’ academic achievement is 79.2%. The results of this study indicate that the hypothesis is accepted, namely that there is a positive and significant effect of Organizational Activeness and Interpersonal Communication Ability on students’ academic achievement, both partially and simultaneously.